Sub-optimal host plants have developmental and thermal fitness costs to the invasive fall armyworm - Mubayiwa, Macdonald; Machekano, Honest; Chidawanyika, Frank; Mvumi, Brighton M.; Segaiso, Bame; Nyamukondiwa, Casper (Frontiers in Insect Science, 2023)
The fall armyworm (FAW) Spodoptera frugiperda (J.E. Smith) is a global invasive pest of cereals. While the pest prefers maize and sorghum as main hosts, it is associated with a wide range of host plants due to its polyphagous nature. Although the FAW's polyphagy is widely reported in literature, few studies have investigated the effects of non-preferred conditions or forms (e.g. drought-stressed forms) of these hosts on the pest's physiological and ecological fitness. Thus, the interactive effects of biotic and abiotic stresses on FAW fitness costs or benefits have not been specifically investigated. We, therefore, investigated the effects of host plant quality on developmental rates and thermal tolerance of the FAW. Specifically, we reared FAW neonates on three hosts (maize, cowpeas and pearl millet), at two levels per host plant [unstressed (well-watered) and stressed (water-deprived)] until adult stage. Larval growth rates and pupal weights were determined. Thermal tolerance traits viz critical thermal maxima (CTmax), critical thermal minima (CTmin), heat knockdown time (HKDT), chill-coma recovery time (CCRT) and supercooling points (SCP) were measured on the emerging adults from each treatment. Results showed that sub-optimal diets significantly prolonged developmental time of FAW larvae, reduced growth rates and ultimate body weight, but did not impair full development. Suboptimal diets (non-cereal plants and drought-stressed cereal plants) increased the number of larval instars to eight compared to six for optimal natural diets (unstressed maize and pearl millet). Apart from direct effects, in all cases suboptimal diets significantly reduced heat tolerance, but effect on cold tolerance was recorded in selected cases e.g., SCP. These results suggest host plant effects on physical and thermal fitness of FAW, indicating a considerable degree of resilience against multiple stressors. The pest's resilience can present major drawbacks to its cultural management using sub-optimal hosts (in crop rotations or intercrops) through ability to survive on most host plants despite their water stress condition and gains in thermal fitness. The fate of FAW population persistence under multivariate environmental stresses is therefore subject to prior environmental host-plant history or quality.